Decolonization of museums from the perspective of Art Education - Simón Sánchez Fernández; Rosario Gutiérrez Pérez (University of Bologna, 2023)
The article presents a theoretical-critical review of the process of decolonization of museums, starting from the new notion proposed by the International Council of Museums (ICOM) at the Kyoto conference (2019). From an epistemological perspective, it problematizes how the forms of acquisition, organization, and transmission of knowledge through collections and exhibitions are being influenced by heritage restitution policies that seek to eliminate the colonial past from European museums. For this reason, and considering that decolonization occupies a central position from which to reassess the social function of the museum, we understand that Art Education is key to breaking the asymmetric intercultural dialogue, addressing deliberate omissions, and amplifying invisibleized imaginaries. This transformation aims for museums to shift from being perceived as legitimizing instruments of hegemony to becoming critical cultural managers, promoters, simultaneously, of new educational proposals based on the knowledge and recognition of diverse epistemologies with which to create other forms of understanding and building culture.